Small Bowel Prolapsed Fhrough Perforated Utérus Following Illegal Induced Abortion.. - DOSSOU, FRANCIS MOÏSE DJIDÉNOU; HOUNKPE, PIERRE-CLAVER; TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; DENAKPO, Justin Lewis; SOHOU, PASCAL (My University, 2012)
Two women were admitted to the emergency service with small bowel prolapsed through the vagina after a curettage for voluntary termination of pregnancy. After a short resuscitation, laparotomy was performed for ileal resection followed by ileo-ileal end to end anastomosis, extensive washing of the abdominal cavity, digital curettage of the uterine cavity, debridement and suturing of uterine perforation. This serious complication of induced abortion is a consequence of the persistence of illegal induced abortion in Sub Saharan Africa. Prevention of this situation could be best archived by better information on contraception, better health education programs and more generally by rising educational attainment of girls.
Keywords: Keywords: Induced abortion; Uterine perforation; Small bowel; prolapsed; Vaginal evisceration; Sub-Saharan Africa